Enhancing Employability, Innovation, Entrepreneurship and Creativity in Changing World - Naik, B. M. (Journal of Engineering Education Transformations, 2017)
Enabling students to learn Innovation in colleges and creating innovative leaders and not only followers is the only pathway to enhance employability and prosperity. Innovative persons never remain idle or jobless. They are always in demand. This is the global experience. Those who realize will win. Others may have all the resources at hand yet they may lose. Tsunami changes are in the offing. Those who learn surfing will stay on the top. What does the future look like for higher education institutions? Will the architecture look like it does today or is there a far more effective model for addressing current problems? You will find answers in this article.